UFERSA vai de bike: desenvolvimento de um sistema de Compartilhamento de bicicletas para a mobilidade no campus Mossoró UFERSA - Silva, Arthur Aleksandro A. (Universidade Federal Rural do Semi-Árido, 2019)
Bike sharing systems are considered a replicable solution that enables and encourages the use of bicycles as a means of transportation. Thus, there is the opportunity to develop, through computing, a bicycle sharing system in order to optimize mobility. Given this, the article aims to present computing experiences in the development of a bicycle sharing system for the context of the UFERSA Mossoró Campus. These experiments combine software and hardware practices and came to define a system consisting of a program for coordinating bicycle stations and other applications, a terminal for stations and two applications for users and administrators. Projects in the context of mobility are complex and require integration between various areas.
Artigo Acadêmico
Keywords: Compartilhamento de bicicleta; Mobilidade; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO